2019
DOI: 10.1002/tox.22871
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA damage and oxidative stress in juvenile Channa punctatus (Bloch) after exposure to multi‐walled carbon nanotubes

Abstract: Multi-walled carbon nanotubes (MWCNTs) have many applications in industry and used as additives in polymers, catalysts, anodes in lithium-battery and drug delivery.There is little information about MWCNTs' (210 nm) genotoxic potential on juvenile freshwater fish Channa punctatus. Therefore, in this study, we have determined the toxic effects of MWCNTs on freshwater fish C. punctatus by assessing toxicological endpoints such as oxidative stress, mutagenicity, and genotoxicity after acute MWCNTs exposure for 5 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Exposed groups were found to have a significantly higher value of these parameters as compared to control showing the genotoxic effect of BPA. Previously DNA damage in spermatozoa of zebrafish ( Lombó et al, 2019 ) and gills and lymphocytes of C. punctatus fish ( Ali et al, 2020 ) due to bisphenol A has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposed groups were found to have a significantly higher value of these parameters as compared to control showing the genotoxic effect of BPA. Previously DNA damage in spermatozoa of zebrafish ( Lombó et al, 2019 ) and gills and lymphocytes of C. punctatus fish ( Ali et al, 2020 ) due to bisphenol A has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of BPA-induced genotoxicity is not very clear but it has been mainly associated with oxidative stress via ROS and lipid peroxidation ( Tiwari et al, 2012 ) which may cause direct DNA abnormalities. DNA damage in different tissues of organisms induced by the generation of free radicals and oxidative stress has been investigated by different researchers ( Ali et al, 2020 , Ghaffar, 2020 , Ghazanfar et al, 2018 , Hussain et al, 2019 )…”
Section: Discussionmentioning
confidence: 99%
“…Following sublethal, acute exposure, genotoxicity at the cellular level in hemocytes and gill tissues was seen for all CuO ENMs, which is consistent with the mussel DNA damage previously reported (Chelomin et al, 2017) and for human cells (Ahamed et al, 2010). Links between oxidative stress and genotoxicity of ENMs have been demonstrated by several authors (Ali et al, 2020; Raghunathan et al, 2013; Song et al, 2012). The effect did not appear to be influenced by coatings, but the greater DNA damage in hemocytes in CuO core ENM exposures suggests an increased hazard from the uncoated material.…”
Section: Discussionmentioning
confidence: 89%
“…Carbon nanotubes (CNTs) are a type of carbon nanomaterial that form hollow tubes with either one layer (single-walled CNTs) or multi-layers [multi-walled CNTs (MWCNTs)] [ 1 ]. CNTs possess outstanding physicochemical properties and biocompatibility, making them widely used in industrial sectors and medicine [ 2 ]. They were used as carriers for the delivery of chemotherapeutics to specifically target cancer cells [ 3 ].…”
Section: Introductionmentioning
confidence: 99%